Relating school leadership to perceived professional learning community characteristics: A multilevel analysis. (July 2016) - Vanblaere, Bénédicte; Devos, Geert
Abstract: This study examines the role of transformational and instructional school leadership in facilitating interpersonal professional learning community (PLC) characteristics (collective responsibility, deprivatized practice, and reflective dialogue). Survey data were collected in 48 Flemish (Belgian) primary schools from 495 experienced teachers. Multilevel analyses, when controlling for school characteristics, demonstrated that instructional leadership is related to perceived participation in deprivatized practice and participation in reflective dialogue. Transformational leadership matters for perceived participation in reflective dialogue but also for the presence of collective responsibility. These findings result in practical implications, based on the distinct merits of both leadership styles for interpersonal PLC characteristics. Highlights: The role of leadership in promoting desirable components of PLCs is underexplored. We examined the distinct merits of instructional and transformational leadership. Analyses were run on self-reported data from experienced primary school teachers. Instructional leaders support deprivatized practice and reflective dialogue. Transformational leaders support reflective dialogue and collective responsibility.